2004
DOI: 10.1016/j.healthpol.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the utilisation of health services in the Ashanti Region, Ghana

Abstract: The survey seeks to structure a model for gender-based health services utilisation for the Ashanti Region of Ghana, and in addition, recommend intervention measures to ensure gender equity in the utilisation of health services. A sample size of 650 covered over 3108 houses, and the main research instruments were the questionnaire and formal interview. A multiple regression model is used for the analysis of the relationship between the complex independent variables and utilisation by gender. Results show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 22 publications
3
36
0
5
Order By: Relevance
“…Comparable results have been reported elsewhere (Kroeger 1983;Kloos et al 1987;Develay et al 1996;Van der Meer et al 1996;Fantahun and Degu 2003;Buor 2004;Ahmed et al 2005). In Ethiopia, most public medical services are cheap; for the poorest even free (Tassew et al 1996;Haile Mariam and Kloos 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Comparable results have been reported elsewhere (Kroeger 1983;Kloos et al 1987;Develay et al 1996;Van der Meer et al 1996;Fantahun and Degu 2003;Buor 2004;Ahmed et al 2005). In Ethiopia, most public medical services are cheap; for the poorest even free (Tassew et al 1996;Haile Mariam and Kloos 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Research has shown that a low rate of health care utilization can be caused by a range of factors, including, monetary and non-monetary costs of receiving care [6][7][8][9], socioeconomic and demographic characteristics of the patients [10][11][12][13][14] and supply side variables such as quality of care [15][16][17]. Given the low level of health care utilization, our goal is to assess the determinants of patient's ambulatory provider choice and to identify those factors that undermine access to care.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios dilucidaron cuestiones como: los factores que afectan el acceso/utilización de servicios de salud (10,(14)(15)(16)19,21,22,25,27,30,41); las diferencias, desigualdades e inequidades en la utilización de servicios de salud (8,12,17,18,31,32,34,35,37); los roles del seguro en la utilización (9,20,26,28,29); las barreras para el acceso/utilización (11,13,23,24,40); las vivencias y expectativas sobre la utilización (33,38,39) y los patrones de uso (36).…”
Section: Tabla 1 Características De Los Estudiosunclassified
“…Las variables del sistema de salud fueron medidas en 41,9 % de los estudios cuantitativos (8,10,11,13,14,16,19,(23)(24)(25)(26)29,37), encontrándose que los factores más estudiados fueron: disponibilidad de recurso humanos y físicos, tipo de servicios, tiempos de espera para obtener una cita, tiempo de espera en el consultorio y políticas institucionales, respectivamente.…”
Section: Figura 1tipo De Variables Explicativas Del Objeto De Estudiounclassified